Adaptation of a school-based mental health literacy curriculum: from Canadian to English classrooms - Rosie Mansfield; Neil Humphrey; Praveetha Patalay; Anna Moore; Emily Stapley (Cambridge Prisms: Global Mental Health, 2021)
Abstract Background School-based mental health literacy (MHL) interventions are increasingly trialled outside of the country in which they were developed. However, there is a lack of published studies that qualitatively explore their cultural adaptation. This study investigated the reasons for adaptations made and suggested to a Canadian MHL curriculum (The Guide) within the English school context.